Accounting Information Quality and Performance of Small and Medium Enterprises in Lagos State - Dorcas ADETULA; Abiola BABAJIDE; Anijesushola AJAYI; Folashade OWOLABI; Omotola EZENWOKE; Oluwole ODETUNMIBI (Communications of International Proceedings, 2021)
Small and Medium Enterprise (SMEs) are crucial to economic development in every nation especially because of their contribution to the Gross Domestic Product (GDP) and employment. However, many of these enterprises have not developed fundamental management capabilities that could enhance robust decision making and ultimately improve performance. One of such capabilities is the ability for such entities to have well established accounting procedures as a means of improving accounting information quality and then their performance. This study examines the association between accounting information quality and performance of small and medium enterprises in Lagos State, Nigeria. The statistical package for the social sciences (SPSS) was adopted for the analysis using cross-sectional survey data of 65 SMEs in Lagos State. The method of data analysis was the bivariate analysis and results showed that there is a significant positive association between accounting information quality and performance of SMEs in Lagos State. This implies that there is a strong connection between the variables examined. The study recommends that SMEs should engage the services of professionals in designing and implementing accounting procedures within their organisations.
Keywords: Accounting information quality; Accounting Procedures; Gross Domestic Product (GDP); Performance; Small and Medium Enterprise (SMEs)